Evaluation of bone marrow in cases of pancytopenia in a tertiary care hospital (Journal of Pathology of Nepal, 2015)
Background: A spectrum of primary and secondary disorders that affect the bone marrow may manifestwith pancytopenia. This study was carried out to identify the various causes of pancytopenia in patients attending a tertiary care hospital in Lalitpur, Nepal.Materials and Methods: A descriptive study of 83 cases of pancytopenia was carried out in the Department of Pathology, Patan Academy of Health Sciences, Lalitpur, Nepal over a two year period from August 2010 to July 2012.Results: Eighty three patients underwent bone marrow examination. Mean age of the patients was 34 years (range: 4 to 75 years). Maximum number of patients (31.33%) was seen in the age group of 16 - 30 years. The commonest cause of pancytopenia was megaloblastic anemia which was seen in 34.94% (29/83) cases followed by aplastic anemia and hematological malignancies in 31.32% (26/83) and 14.46% (12/83) cases, respectively.Conclusion: This study concluded that megaloblastic anemia and aplastic anemia were the two most common causes of pancytopenia. Bone marrow aspiration is an established diagnostic modality in the evaluation of pancytopenia.Journal of Pathology of Nepal (2015) Vol. 5, 691 - 695